Ambient Air Pollution and Hospitalization for Acute Myocardial Infarction in Chongqing, China: A Time-Stratified Case Crossover Analysis - Zhao, Mingming; Liu, Xing; Yuan, Ming; Yang, Ying; Chen, Hao; Li, Mengmeng; Luo, Pan; Duan, Yong; Fan, Jie; Liu, Leqi; Zhou, Li (Frontiers in Physics, 2022)
Previous studies have demonstrated that short-term exposure to ambient air pollution was associated with hospital admissions for cardiovascular diseases, but the evidence of its effects on acute myocardial infarction (AMI) in East Asian countries is limited and inconsistent. We aimed to investigate the association between air pollution and AMI hospitalizations in Chongqing, China. This time-stratified case-crossover study included 872 patients with AMI from three hospitals in Chongqing from January 2015 to December 2016. Exposures were compared between days with AMI (case days) and days without AMI (control days). Spearman correlation coefficient was applied to explore the correlation between air pollutants and meteorological conditions. Conditional logistic regression was used to assess the associations between air pollution exposure with different lag periods and AMI hospitalizations. Stratification analysis was further implemented by sex, age, and season. Hospitalizations for AMI were signiﬁcantly associated with air pollution. All analyzed air pollutants showed lag-specific at lag 0 day and lag 01 day, whereas a 10 µg/m3 increase of average concentrations in PM2.5 , PM10, SO2, NO2, CO was associated with 1.034%(95% CI: 1.003-1.067%) , 1.035%(95% CI:1.015-1.056%) , 1.231%(95% CI: 1.053-1.438%) , 1.062%(95% CI: 1.018-1.107%), 1.406%(95% CI: 1.059-1.866%) increase in hospitalizations for AMI, respectively. No effect modifications were detected for sex, age, and season. Our findings suggest that short-term exposure to PM2.5, PM10, SO2, NO2, and CO contributes to increase AMI hospitalizations, which have public health implications for primary prevention and emergency health services.